Effect of Chemical Reaction on Mass Transfer Embedded in a Porous Medium over an Exponentially Porous Stretching Surface - Amoo, S.A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
The effect of chemical reaction on mass transfer embedded in porous medium is implemented over an exponentially porous stretching surface. The emerging governing equations were simplified using similarity variable function and some relevant dimensionless parameters. The modelled equations were solved using Runge-Kutta method with shooting techniques. This was done by converting the modelled equations to an initial value problem and solved using Maple 18. The numerical computations were presented in tabular and graphical forms for variable fluid parameters controlling the flow, chemical reaction and mass transfer. The results in form of velocity and concentration profiles, Skin friction and Sherwood number increased with varied parameters were discussed. The findings were compared with existing solutions and found to have minimal errors.